China’s Utilization of the Paris Agreement’s ‘CBDR-RC’ Principle Through the Role of Identity - Avathari, Putu Audrey Shasika (Journal of World Trade Studies, 2025)
This study examines China’s utilization of the Common but Differentiated Responsibilities and Respective Capabilities (CBDR-RC) Principle to justify its Nationally Determined Contributions (NDCs) under the Paris Agreement. As the world’s largest carbon emitter and a major economic power, China faces mounting international pressure to undertake ambitious climate commitments, especially after its NDCs are evaluated as ‘insufficient’ in meeting the Paris Agreement 1.5C goal. Through the Constructivist lens of International Regime Theory, this study explores how China uses the role of identity to institutionalize CBDR-RC in the Paris Agreement, where China uses its type identity as a developing nation and role identity as the leader of the Global South to shape climate negotiations; it also forms a collective identity with the Global South countries through alliances to promote the institutionalisation of the CBDR-RC principle. Using the methods of Political Discourse Analysis and Process Tracing, this study highlights China’s active role in institutionalizing CBDR-RC in the Paris Agreement to ensure the rights to differentiated climate obligations and preferential treatment for developing nations in the climate regime, which ultimately allows China to justify its NDCs under the CBDR-RC principle through the logic of appropriateness.